Pre-Cerclage cervical length predicts long-term pregnancy sustenance: A case-control study. (September 2022) - Kondo, Emi; Shibata, Eiji; Sakuragi, Toshihide; Aiko, Yukiyo; Kawakami, Takeshi; Takashima, Takeshi; Yoshino, Kiyoshi; Okura, Naofumi
Abstract: Background: This study aimed to assess a predictor of long-term pregnancy sustenance post cervical cerclage in women with or without a medical history of cervical insufficiency. Materials and methods: We included pregnant women who underwent cerclage at 12–25 weeks gestation in four perinatal medical centers between January 2009 and December 2010. We classified the cerclage modality as ultrasound-indicated cervical cerclage if the pre-cerclage CL was <25 mm because the prophylactic and therapeutic cerclage definitions varied among institutions. The procedure was deemed successful if the pregnancy continued for more than 13 weeks post cerclage. We compared the outcomes of women who underwent successful and unsuccessful cerclage and investigated whether the pre-cerclage CL could predict pregnancy outcomes in women who underwent successful cerclage using receiver-operating characteristic curves. Results: We screened 114 pregnant women; 91 met the inclusion criteria. Pre-cerclage CL was a moderately accurate predictor of long-term pregnancy sustenance in the successful group (optimal cut-off value: 17 mm; area under the curve: 0.76; P = 0.0016). Approximately 87% of patients with a pre-cerclage CL ≥ 17 mm sustained their pregnancies for more than 13 weeks post cerclage; however, 64% of patients with a pre-cerclage CL < 17 mm did not. Conclusion: We speculate that the use of other treatment options in addition to cerclage in women with a pre-cerclage CL < 17 mm may result in a successful pregnancy. Highlights: Cervical cerclage encompasses many indications and specific techniques. Pre-cerclage cervical length (CL) predicts long-term pregnancy sustenance. 87% women (pre-cerclage, CL ≥ 17 mm) sustained their pregnancy for >13 weeks. 64% women (pre-cerclage, CL < 17 mm) did not sustain their pregnancy for >13 weeks. Cerclage can be considered in women with a pre-cerclage CL < 17 mm.